Numerical modeling of fiber reinforced polymer textile composites for characterizing the mechanical behavior – a review. Issue 10 (5th October 2022) - Kaushik, V.; Sharma, P.; Priyanka, P.; Mali, H.S.
Abstract: Polymeric composites are used worldwide due to their enhanced applications in various sectors such as automotive, defense, aerospace, marine, and many others. Its lightweight and high‐strength applications make it convenient to use in high‐security fields such as defense and aerospace. Thus, it is essential to characterize composite materials for product development. Numerical simulation of composites has advantages over experimental characterization. The paper presents the mechanical behavior of polymer textile composites, employing geometrical modeling and a numerical simulation approach, under several loading conditions such as tension, compression, flexural, and impact loading. Failure mechanisms are also discussed with different failure modes and damage criterions. This review paper is limited to high‐strength fibers, such as carbon, Kevlar, and Glass fibers in unidirectional and woven formation. Various test specimens used in mechanical characterizations are presented with significant research summaries. Classification charts are also provided for a better understanding of the numerical simulation approach for characterizing the mechanical behavior. Abstract : An exhaustive review of geometric modeling, numerical characterization, failure mechanisms, and applicability of high‐strength fiber reinforced polymer textile composites in various sectors are described. Unidirectional, plain, and twill woven fibrous composites are considered for review to understand mechanical behavior under tension, compression, flexural and impact with various failure mechanisms.